Life Style Education: Are We Prepared for Changes? - Qismullah Yusuf (Universitas Syiah Kuala, 2016)
The public should be aware of the sudden change of life style of some people that makes their life completely different from their previous ones. All of us must be ready to face any circumstances from this manifestation in the future.  The rich, wealthy and famous should be made aware that that type of life style is not wrong, but they should also be taught how to follow a normal way of life. Proper guidance and counselling on how to live normally needs to be provided with especially designed lectures and classes. Bringing these "students" to remote villages where the poor and the disadvantaged live may help them to understand the hardships of life around them. Having a short intern period within such a community will help them further understand the real life of the majority in their country. Furthermore, if they are always taught in an environment of luxury and are never faced with a normal education system and style of life, a major problem arises: if, in the future, our country is led by such graduates, who never went through our normal education system or lived a normal style of life, how can they understand and lead the majority in our country? This paper discusses this phenomenon.